Chalk, Wabaunsee County - Spachek, Michael (Kansas State University, The Chapman Center for Rural Studies, 2016)
This paper will tell the story of Chalk, Kansas, from the initial settlement in the 1850s to the last business closing in 1956. It will focus on the story of blacksmiths in Chalk and specifically John Crisp, the blacksmith in business there for fifty years. The three blacksmiths who served the Chalk Mound area supported a landscape of black and white farming and ranching. Rock Creek Township in Wabaunsee County was home to a racially integrated community between 1880 and 1900, and Chalk held isolated rural farm families together. The closing of the post office in 1907 ended Chalk’s development. This study uses plat maps, newspaper articles, two important newspaper columns, site studies, and informal interviews.
Michael Spachek, “Chalk, Wabaunsee County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/168.
Keywords: African American Farmers; Alma; Chalk Mound; Exodusters; Wabaunsee County; Rock Creek